Pengetahuan dan Sumber Informasi Berhubungan dengan Tindakan Pemeriksaan Payudara Sendiri pada Siswi SMA - Ningsi, Agustina; Mukarramah, Sitti; Cahyanti, Arika (Jurnal Kebidanan Malakbi, 2021)
Breast Self-Examination (BSE) is the development of a woman's concern for the condition of her own breasts. Breast cancer is a malignant tumor that grows in the breast tissue. The incidence of breast cancer reaches 42.1 per 100,000 population with an average death rate of 17 per 100,000 population. BSE on a regular basis is an important step for early detection of breast cancer. This study aims to determine the relationship between knowledge and sources of information about breast self-examination with early detection of breast cancer in female students of SMA Muhammadiyah 5 Tallo, Makassar City, using an analytic survey method and a Cross Sectional Design. The subjects of this study were young women in SMA Muhammadiyah 5 Tallo Makassar City with a population of 53 respondents who were taken by total sampling. Statistical analysis used in this study is Chi-Square statistic, with a confidence level of É‘=0.05. Based on the results of the study, it is known that the knowledge significance value is P = 0.001 (p < 0.05) with a coefficient value (Phi = 0.465), the source of information is p = 0.000 (p < 0.05) with a coefficient value (Phi = 0.635). So it can be concluded that there is a relationship between knowledge and sources of information about breast self-examination at SMA Muhammadiyah 5 Tallo Makassar City. It is recommended for education providers and health workers to increase counseling about breast self-examination.